The Encapsulation of Hemagglutinin in Protein Bodies Achieves a Stronger Immune Response in Mice than the Soluble Antigen - Hofbauer, Anna; Melnik, Stanislav; Tschofen, Marc; Arcalis, Elsa; Phan, Hoang T.; Gresch, Ulrike; Lampel, Johannes; Conrad, Udo; Stoger, Eva (Frontiers in Plant Science, 2016)
Zein is a water-insoluble polymer from maize seeds that has been widely used to produce carrier particles for the delivery of therapeutic molecules. We encapsulated a recombinant model vaccine antigen in newly formed zein bodies in planta by generating a fusion construct comprising the ectodomain of hemagglutinin subtype 5 and the N-terminal part of γ-zein. The chimeric protein was transiently produced in tobacco leaves, and H5-containing protein bodies (PBs) were used to immunize mice. An immune response was achieved in all mice treated with H5-zein, even at low doses. The fusion to zein markedly enhanced the IgG response compared the soluble H5 control, and the effect was similar to a commercial adjuvant. The co-administration of adjuvants with the H5-zein bodies did not enhance the immune response any further, suggesting that the zein portion itself mediates an adjuvant effect. While the zein portion used to induce protein body formation was only weakly immunogenic, our results indicate that zein-induced protein bodies are promising production and delivery vehicles for subunit vaccines.